Electroelastic bulk and normal shear waves in a layered-periodic medium of the type metal-piezoelectric-dielectric - Levchenko , V. (Energy and Automation, 2025)
A method for constructing dispersion relations for bulk and normal electroelastic shear waves propagating in layered-periodic media formed by repeating a "generating" metallized package consisting of a piezoelectric layer and a dielectric layer that has no electrical properties is proposed. As a result of the analytical calculations, dispersion relations for normal and bulk electroelastic shear waves were obtained. CdS or ZnO were considered as piezoelectric materials, and the dielectric layer was chosen with the parameters GaYIG. The obtained dispersion relations were numerically analyzed for different geometries and physical properties of the materials forming the "generating" package. . Numerical analysis showed that a feature of the obtained bulk wave spectrum is that in the range of changes in the wave number and circular frequency, the zone boundaries do not intersect. The spectrum of normal waves is localized in the transmission zones of bulk waves except for one dispersion curve. The influence of physical, mechanical and geometric parameters of the layers on the structure of the blocking and transmission zones has been studied, as well as the influence of the piezoelectric effect has been investigated.Based on the approach proposed in the works of M.O. Shulga, the problems of bulk and normal electroelastic waves are reduced to the study of the properties of the transmission matrices of the "generating" package of layers, through the elements of which the desired dispersion relations are expressed. In the work, it was possible, using the condition of metallization on the outer surfaces of the package, to write the dispersion relations through the elements of second-order matrices instead of the fourth, which allows simplifying the analysis of the dispersion equations.Key words: bulk and normal shear waves, periodic layered structure, piezoelectric, dielectric, transmission zones, bulk wave blocking zones